Bagaimanakah komunikasi matematis calon guru? studi pendahuluan pada mahasiswa calon guru sekolah dasar - Ristiana, Muhammad Ghiyats; Wahyudin; Herman, Tatang; Nurjanah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
Teaching mathematics should be communicated properly to students, so they can understand the whole concept, especially teaching in primary school. Nowadays, some teachers teaching mathematics just to make students memorize the concepts, not understand the whole concepts. This may cause when they were still become students to learn in university, they didn’t understand mathematics well enough. Therefore, the purpose of this study is to explain how well mathematical communication ability of prospective primary school teachers. To do so, we used qualitative descriptive approach using mathematical communication test to collect data from a group of prospective elementary school teachers. Data were analyzed by categorizing each indicator to identify factors that affect their mathematical communication ability. The results shows that mathematical communication ability of prospective primary school teachers is still in moderate category and tends to be in low category. An overview of each factor based on mathematical communication ability indicators will be shown in this research. These findings emphasize the need for improving prospective primary school teachers’ mathematical communication ability to make their preparation more thorough before carrying out teaching.